Media Sosial di Tempat Kerja Saat dan Pasca Pandemi Covid-19 : Sebuah Tinjauan Literatur Sistematis - Aji Buana, Dwinto Martri; Rahmayanti, Rima; Hayati, Neuneung Ratna; Sukandi, Pipin; Sofyandi, Herman; Agustriyana, Darwis; Aji Soedjai, Achmad Drajat (Jurnal Sosioteknologi, 2025)
Social media in the workplace is a contemporary phenomenon that plays a crucial role in various aspects of organizational life. However, its dynamics during the COVID-19 pandemic and the subsequent new normal have been rarely explored in the literature. This study aims to fill this gap by analyzing existing literature on social media usage in the workplace during these unprecedented times. We systematically identified and reviewed selected publications from the Web of Science (WOS) and Scopus databases. Through an in-depth investigation, we elucidate the dynamics of social media amidst a crisis that has impacted all facets of life. The results of this study not only reveal, summarize, and critically examine various social media phenomena in the workplace during the COVID-19 pandemic and the new normal period but also highlight their implications for future research. Our findings suggest several promising avenues for further exploration, emphasizing the need for a deeper understanding of this topic. The paper concludes with recommendations for future research opportunities that could enhance our comprehension of social media’s role in the evolving workplace landscape.